Entrepreneurship ecosystems and women entrepreneurs: a social capital and network approach - Neumeyer, X.; Neumeyer, X.; Santos, S. C.; Caetano, António; Pamela Kalbfleisch (Small Business Economics, 2019)
This study investigates the effects of venture typology, race, ethnicity, and past venture experience on the social capital distribution of women entrepreneurs in entrepreneurial ecosystems. Social network data from two municipal ecosystems in Florida, USA (Gainesville and Jacksonville), suggest that network connectivity and the distribution of social capital are significantly different for men and women entrepreneurs. This difference is contingent on the venture type. Male entrepreneurs show higher comparative scores of bridging social capital in aggressive- and managed-growth venture networks, while women entrepreneurs surpass their male counterparts’ bridging capital scores in lifestyle and survival venture networks. Lastly, experienced women entrepreneurs that self-identified as white showed a higher degree of network connectivity and bridging social capital in the entrepreneurial ecosystem than less experienced non-white female entrepreneurs. Implications for entrepreneurship practice and new research paths are discussed.